Food, sacrifice, and sagehood in early China - Sterckx, Roel, 1969- (Cambridge ; New York : Cambridge University Press, 2011)
"In ancient China, the preparation of food and the offering up of food as a religious sacrifice were intimately connected with models of sagehood and ideas of self-cultivation and morality. Drawing on received and newly excavated written sources, Roel Sterckx's book explores how this vibrant culture influenced the ways in which the early Chinese explained the workings of the human senses, and the role of sensory experience in communicating with the spirit world. The book, which begins with a survey of dietary culture from the Zhou to the Han and offers some intriguing insights into the ritual preparation of food--some butchers and cooks were highly regarded and would rise to positions of influence as a result of their culinary skills--and the sacrificial ceremony itself. As a major contribution to the study of early China and to the development of philosophical thought, the book will be essential reading for students of the period, and for anyone interested in ritual and religion in the ancient world"--Provided by publisher.
Customs and cuisine -- Cooking the world -- Sacrifice and sense -- The economics of sacrifice -- Sages, spirits, and senses.
Includes bibliographical references (p. 207-226) and index.
Description based on print version record.
Keywords: Confucianism -- Rituals -- History -- To 1500.; Food -- China -- Religious aspects -- History -- To 1500.; Food habits -- China -- History -- To 1500.; Rites and ceremonies -- China -- History -- To 1500.; Sacrifice -- Confucianism -- History -- To 1500.; Senses and sensation -- Religious aspects -- Confucianism -- History -- To 1500.; Philosophers -- China -- History -- To 1500.; China -- Kings and rulers -- History; China -- Religious life and customs; China -- History -- Han dynasty, 202 B.C.-220 A.D.; HISTORY / Asia / General; RELIGION / Eastern; Electronic books